2014
DOI: 10.2298/sos1401015i
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sintering temperature on electrical and microstructure properties of hot pressed Cu-TiC composites

Abstract: In this study, Cu-TiC composites were successfully produced using hot pressing method. Cu-TiC powder mixtures were hot-pressed for 4 min at 600, 700 and 800?C under an applied pressure of 50 MPa. Phase composition and microstructure of the composites hot pressed at different temperatures were characterized by X-ray diffraction, scanning electron microscope, and optic microscope techniques. Microstructure studies revealed that TiC particles were distributed uniformly in the Cu matrix. With the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 16 publications
0
23
0
3
Order By: Relevance
“…The formation of Cu(Ti, C) solid solution enhances the hardness of the composites. As the sintering temperature increases, there is a significant increase in the hardness values because more TiC particles precipitate after the reaction between Ti and C. The highest hardness value of an ex-situ Cu-Ti-C composite with 10 vol % of TiC was found to be about 86.4 HV [7], much lower than those found for the in-situ produced nanocomposites of this work, which were 295 and 290 HV respectively for Cu-TiH2-C and Cu-Ti-C nanocomposites with the same TiC content and sintered at 900 • C. By increasing the volume of TiC, the hardness of nanocomposites also increases to 314 and 306 HV correspondingly for Cu-TiH2-C and Cu-Ti-C nanocomposites when sintered at 1000 • C. at the sintering temperature of 900 °C, hardness values of Cu-Ti-C nanocomposites are lower than those for Cu-TiH2-C nanocomposites, for any addition of TiC. The formation of Cu(Ti, C) solid solution enhances the hardness of the composites.…”
Section: Hardness Results Of Compactsmentioning
confidence: 96%
See 2 more Smart Citations
“…The formation of Cu(Ti, C) solid solution enhances the hardness of the composites. As the sintering temperature increases, there is a significant increase in the hardness values because more TiC particles precipitate after the reaction between Ti and C. The highest hardness value of an ex-situ Cu-Ti-C composite with 10 vol % of TiC was found to be about 86.4 HV [7], much lower than those found for the in-situ produced nanocomposites of this work, which were 295 and 290 HV respectively for Cu-TiH2-C and Cu-Ti-C nanocomposites with the same TiC content and sintered at 900 • C. By increasing the volume of TiC, the hardness of nanocomposites also increases to 314 and 306 HV correspondingly for Cu-TiH2-C and Cu-Ti-C nanocomposites when sintered at 1000 • C. at the sintering temperature of 900 °C, hardness values of Cu-Ti-C nanocomposites are lower than those for Cu-TiH2-C nanocomposites, for any addition of TiC. The formation of Cu(Ti, C) solid solution enhances the hardness of the composites.…”
Section: Hardness Results Of Compactsmentioning
confidence: 96%
“…In composites produced in-situ, the interfacial area is higher compared to ex-situ composites, detrimental effects of interfacial phenomena (decohesion, void formation) are more likely to prevail at high sintering temperatures compared to low sintering temperatures. Islak et al [7] reported that in hot-pressed Cu-Ti-C nanocomposites, with 10 vol % TiC, the highest relative density obtained was about 86.4%, while in our samples, with the same TiC content, it is, on average, around 96.8 either for Cu-TiH2-C or Cu-Ti-C nanocomposites sintered at 1000 • C. The presence of porosity on the surface of nanocomposites is a natural result of the consolidation process. The relative density of Cu-TiH2-C has higher than that of Cu-Ti-C composite that why the amount of porosity can be seen in Figure 4b,d is more than in Figure 4a,c, respectively.…”
Section: Characterization Of Compacts After Spsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the microstructure image of the composite in Figure 4a is examined, it can easily be seen that the boron carbide grains are homogeneously distributed in the MgAl matrix. It is strongly emphasized in the literature that if reinforced particles distribute homogeneously, this situation would positively affect the mechanical properties of the composite [27,28]. In addition, point and area EDS analyses are also seen in the microstructure.…”
Section: Discussionmentioning
confidence: 99%
“…Meydana gelen akım, uygulanan elektriksel alanın şiddeti ve çarpışma frekansı ile belirlenen ortalama elektron hızı ile orantılıdır. İdeal bir kristalde elektronlar dirençle karşılaşmadan hareket ederler [13]. Fakat gerçek kristallerde elektronlar fononlar, dislokasyonlar, boşluklar yabancı katkı atomları ve herhangi kafes kusurlarıyla çarpışırlar.…”
Section: Elektriksel öZellikler (Electrical Properties)unclassified